A filosofia perene segundo Aldous Huxley e a controvérsia sobre a natureza universal do misticismo - Andrade, Camila Santos (2022)
The present thesis aims to discuss aspects of mysticism as seen by Aldous Huxley in his The Perennial Philosophy (1945) and the contemporar y discussions on the nature of mystical experience in the Science o f Religion. The Huxley po sitions, a short intellectual biography, the world situation in his youth, a chronology of his achievements, and some of his best-known critics of the perenniality of the religious phenomenon are presented. A short analysis of the positions on mystical experiences preceded the analysis of their constitutive elements to indicate that the specific languages of the different esoteric schools are essential for their description, being certain that there is no similarity in these events and, even less, identity in their processes. From the systemic constructionism that takes into account the dynamics of society as a long-lasting socio-historical process and, therefore, endowed with locality and glocality, the perenialist conceptions were discarded as inappropriate to describe what it intends to explain